Pandemic influenza A vs seasonal influenza A in hospitalized children in Athens. (February 2015) - Stripeli, F.; Logotheti, I.; Vraila, V. M.; Balta, C.; Patsioura, A.; Papaevangelou, V.; Papadatos, I.; Baka, A.; Tsiodras, S.; Tsolia, M. N.
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Data on pandemic H1N1 influenza (pH1N1) virus infection in hospitalised children are limited. Aims and Objectives: To examine the epidemiological and clinical characteristics of children hospitalised with pH1N1 at a large tertiary-care centre in Athens and compare them with those of children hospitalised with seasonal influenza A in previous years. Methods: All children (n = 146) admitted with confirmed pH1N1 between October 2009 to February 2010 and January 2011 to May 2011 were included. Data on children ≧6 months of age (n = 109) were compared with those of 138 children admitted with seasonal influenza A who were examined during two previous influenza seasons (2002–2003 and 2004–2005). Results: The age distribution was similar between seasonal and pandemic H1N1. Bronchial asthma was significantly more common in the seasonal influenza group but the clinical presentation was similar in the two groups, except that fever was more common in patients with pH1N1. Children admitted with seasonal influenza were more likely to develop acute otitis media. There were no significant differences between the two groups for severe outcomes (admission to the ICU, mechanical ventilation or death). Only one child with seasonal influenza (0·6%) and three with pH1N1 influenza (2%) required admission to the ICU. Mean length of hospitalisation was longer in the seasonal influenza group. Conclusion: Clinical manifestations were similar between pH1N1 and seasonal influenza, and the pandemic virus did not appear to cause more severe disease in hospitalised children.